Pembentukan Karakter Profil Pelajar Pancasila Dimensi Beriman dan Bertaqwa Melalui Penerapan Kegiatan Pembiasaan Shalat Dhuha pada Siswa Kelas IV Sekolah Dasar Negeri 01 Trengguli Jenawi Karanganyar Tahun Pelajaran 2023/2024 - Wulandari, Wulandari; Sutrisno, Tri; Mahendra, Moefty (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
The aim of this research is to describe the implementation of the Dhuha Prayer habitual activity in forming the Pancasila Student Character Profile Dimension of Faith and Devotion in Class IV Students at Trengguli 01 Jenawi Karanganyar State Elementary School. This research uses a qualitative descriptive approach. The subjects in this research were 4th grade students at SD Negeri 01 Trengguli, Jenawi District. The data collection techniques used were observation, interviews and documentation. The data analysis technique uses qualitative data analysis techniques with three stages, namely data reduction, data presentation, and drawing conclusions. The validity of the researcher's data uses source triangulation. The results of this research show that SD Negeri 01 Trengguli has implemented the Pancasila student profile program by holding Dhuha prayer habituation activities carried out by all students. The elements of the dimension of faith and piety that are developed are a.) religious morals, students respect each other between religions, b.) personal morals, students feel confident and disciplined in performing the Duha prayer, c.) human morals, students are taught to collaborate with other friends, d.) morals in nature are accustomed to loving the cleanliness of the school environment, e.) state morals apply the first principle of Pancasila. The obstacle to getting used to Duha prayers is the lack of several facilities that can support the activities of getting used to Duha prayers.